Predicting Dissolved Lignin Phenol Concentrations in the Coastal Ocean from Chromophoric Dissolved Organic Matter (CDOM) Absorption Coefficients - Fichot, Cédric G.; Benner, Ronald; Kaiser, Karl; Shen, Yuan; Amon, Rainer M. W.; Ogawa, Hiroshi; Lu, Chia-Jung (Frontiers in Marine Science, 2016)
Dissolved lignin is a well-established biomarker of terrigenous dissolved organic matter (DOM) in the ocean, and a chromophoric component of DOM. Although evidence suggests there is a strong linkage between lignin concentrations and chromophoric DOM (CDOM) absorption coefficients in coastal waters, the characteristics of this linkage and the existence of a relationship that is applicable across coastal oceans remain unclear. Here, 421 paired measurements of dissolved lignin concentrations (sum of 9 lignin phenols) and CDOM absorption coefficients (ag(λ)) were used to examine their relationship along the river-ocean continuum (0-37 salinity) and across contrasting coastal oceans (sub-tropical, temperate, high-latitude). Overall, lignin concentrations spanned four orders of magnitude and revealed a strong, non-linear relationship with ag(λ). The characteristics of the relationship (shape, wavelength dependency, lignin-composition dependency) and evidence from degradation indicators were all consistent with lignin being an important driver of CDOM variability in coastal oceans, and suggested physical mixing and long-term photodegradation were important in shaping the relationship. These observations were used to develop two simple empirical models for estimating lignin concentrations from ag(λ) with a +/- 20% error relative to measured values. The models are expected to be applicable in most coastal oceans influenced by terrigenous inputs.